The impact of capital structure on bank profitability: evidence from Vietnam - Nam Hai Pham; Tri M. Hoang; Nhung Thi Hong Pham (Cogent Business & Management, 2022)
The purpose of this research is to determine the effect of capital structure on the profitability of Vietnamese commercial banks. Specifically, it investigates the relationship between capital structure and profitability using an imbalanced panel data set of Vietnamese commercial banks from 2012 to 2018, a critical period for implementing the Prime Minister’s decision (254/QD-TTg) on restructuring the Vietnamese commercial banking system. To depict the capital structure of Vietnamese commercial banks, the authors employ customer deposits and non-deposit liabilities. The study findings, based on a dataset of 30 Vietnamese commercial banks, indicate that customer deposits have a negative effect on bank profitability, whereas non-deposit liabilities have a positive effect on bank profitability. Study findings imply that Vietnamese commercial banks should conduct more thorough and equitable evaluations before lending to assure the quality of both assets and loans. Additionally, it is essential to conduct a more thorough analysis of investment projects and long-term loans to assure the bank’s asset quality. This study contributes to the existing literature by examining how capital structure affects the profitability of Vietnamese commercial banks, an area where prior research has been deficient.